ANALISIS PROGRAM LITERASI DALAM MENINGKATKAN KEMAMPUAN MEMBACA SISWA DI SDN 3 PAGAR ALAM - Dewi, Rahmipa Sulistya; Nurlis (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
This research aims to examine the implementation of reading and writing literacy programs, especially the "15 minutes of reading before learning" activity, in improving the reading ability of lower grade students at SD Negeri 3 Pagar Alam. Furthermore, this study also identifies the supporting and inhibiting factors in its implementation. The background of this research is based on the lack of reading ability among 3C class students and individual obstacles in the learning process. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research population was all 155 students in class 3, with a sample of 8 students selected through purposive sampling. The results show that the 15-minute reading literacy program before learning is effective in improving students' reading ability. However, several inhibiting factors were found, such as irregular library schedules, poor book conditions, and variations in student characteristics. Meanwhile, supporting factors include the active role of teachers, the availability of facilities, and the enthusiasm of some students.